The hyper-enrichment of silver through the aggregation of silver sulfide nanoparticles - Mingchun Chai; Anthony E. Williams-Jones; Wei Fu; Jianwei Li; Cheng Xu (Nature Communications)
Abstract Silver deposits have long been considered to form due to the direct precipitation of silver minerals from aqueous fluids, in which the metal is transported as chloride and/or bisulfide complexes. Ultra-high-grade silver ores have silver contents up to tens of weight-percent in the form of silver sulfides and native silver. Ore-forming fluids of most silver deposits, however, typically contain low silver contents of parts per million silver. The challenge is to explain how fluids with such low concentrations of silver can form ultra-high-grade silver ores. Here, we present direct mineralogical evidence from natural samples showing that the high-grade silver ores form from the aggregation of silver sulfide nanoparticles through intermediate microparticles and dendrites to acanthite crystals. Native silver grows from silver sulfides via solid-state silver ion aggregation. This study traces the formation of silver sulfides from their nanoparticulate precursors, thereby providing insights into the genesis of ultra-high-grade silver ores in a variety of metallogenic settings.